Acervo Fotográfico do Museu da Universidade Federal do Pará – MUFPA: análise dos métodos de preservação - DIAS JUNIOR, Carlos Daniel do Amaral (2022)
Analysis of preservation methods applied at the museum of the Federal University of Pará - MUFPA, focusing on the collection of photographs related to the Federal University of Pará - UFPA - parties, birthdays, dean images and the museum's internal space - identifying how these methods were applied in the collection. The research was conducted through a case study, character, bibliographic and qualitative, in which field visits were made to the MUFPA collection to obtain information about it. The research identified that, despite localized efficient practices, the collection needs adjustments to improve its preservation strategies.